Production Enhancement of Condensate Reserves By Рeriodic Well Shutdowns Method - V. V. Inyakin (Наука. Инновации. Технологии)
Introduction. During the development of gas condensate deposits for depletion, with a decrease in reservoir pressure, condensate falls out in the bottomhole zone of wells (BWZ) and a zone with increased condensate saturation is formed.Materials and methods of research. The considered method of non-stationary operating mode was justified by the example of the development of the Achimov deposits of the Urengoyskoye field using the tNavigator software package.Research results and their discussion. The work studies a method of periodical shutting down a gas condensate well in order to increase the additional recovery of retrograde condensate from the reservoir. The optimal well shutdown period is substantiated through the use of hydrodynamic modeling. The paper also analyzes the factors aimed at maintaining the maximum effect from the periodic operation of the well, the main of which is the mode of operation after the well is launched. The considered method of non-stationary operating mode was justified by the example of the development of the Achimov deposits of the Urengoyskoye field using the tNavigator software package. The initial information for modeling was the following: monthly operational reports (MER); results of gas condensate studies; downhole and wellhead measurement data.Conclusion. Based on the studies performed to determine the optimal duration of well shutdown during the development of the Achimov deposits of the Urengoyskoye field, it was revealed that the shutdown duration (more than 183 days) will have a negative impact on the potential condensate content in the formation gas. It has been substantiated that the efficiency of periodic shutdowns is affected by the technological mode of well operation after start-up. Also, the drawdown reduction makes it possible to preserve the effect of the reverse dissolution of condensate through the use of the natural energy of the reservoir.